EL CONSUMO TRANSFRONTERIZO, SU PROBLEMA Y SITUACIÓN SOBRE SU TRATAMIENTO EN EL PERÚ - Freitas Vela, Freddy (Revista de Derecho, 2019)
The present investigation deals with the problem of cross-border consumers facing the current and growing globalization of direct and virtual commerce. Likewise, it shows us which are the main difficulties that have arisen both in the previous stages of the consumer relationship, and at the same moment in which the relationship is formed as well as in the post-sale; given the potential distance between consumer and supplier, the different applicable laws and the competent authority to process a claim. Many of these problems have not yet been resolved, definitively, by the authorities of consumer protection in the world and there are many international organizations that recommend the adoption of various policies and standards that aim to mitigate, correct or seek solutions for these problems, all of which are still in the extra process and auto composition level since the consumer protection authorities have failed to either establish effective collaboration mechanisms, or the conflict of the local jurisdiction is not overcome. In Peru, the rules of the Code for the Protection and Defense of the Consumer, applicable to cases of cross-border consumption with effects in our country, have been interpreted to the benefit of Peruvian consumers who perform these operations. However, its practical application is still quite complicated and economically burdensome, adding to the questionable effectiveness of the procedure against a foreign supplier. At the same time, INDECOPI, the consumer authority in Peru, continues to make efforts to try to provide consumers with innovative tools and technology that help solve their consumption problems. Some of these, such as the next interactive platform to manage claims will also allow to solve problems of a cross-border nature. Likewise, the agreement with its Chilean counterpart, SERNAC, is an important and innovative model that seeks to provide consumers with an instrument in the face of potential problems that could arise in the massive cross-border consumption relationships that are made between citizens of both countries.